2015
DOI: 10.7763/ijmmm.2015.v3.161
|View full text |Cite
|
Sign up to set email alerts
|

Study of Corrosion Resistance of Aluminum Alloy 6061/SiC Composites in 3.5% NaCl Solution

Abstract: Abstract-This paper aims to study the corrosion resistance of metal matrix composite of an aluminum alloy (Al 6061) reinforced by SiC particles with 10wt% and 20wt%. Composite materials were prepared by stir casting using vortex technique. Corrosion behavior of aluminum matrix composite in sea water (3.5% NaCl solution) was examined using potentiostatically polarization measurements. The corrosion rate was calculated by Tafel equation and from the achieved polarization results. It was found that adding of SiC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The corrosion behavior of the Al-SiC composite has been reported contradictorily by different authors. Some of them reported that Al-SiC composite shows better corrosion resistance as compared to Al alloy [18,19], while some of the authors reported low corrosion resistance in the case of Al-SiC composite as compared to Al alloy [20][21][22]. The finer size of SiC particles has better corrosion resistance as compared to the bulky particles [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion behavior of the Al-SiC composite has been reported contradictorily by different authors. Some of them reported that Al-SiC composite shows better corrosion resistance as compared to Al alloy [18,19], while some of the authors reported low corrosion resistance in the case of Al-SiC composite as compared to Al alloy [20][21][22]. The finer size of SiC particles has better corrosion resistance as compared to the bulky particles [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Zakaria (2014) studied the effect of size and volume fraction of SiC particles on corrosion behavior of pure aluminum matrix composites in 3.5% NaCl solution and found that the corrosion rate increased with increasing the duration exposure. Abbass, Hassan, and Alwan (2015) found that adding SiC particles in 10% and 20% to Al6061 alloy matrix increased the corrosion rate in 3.5% NaCl solution.…”
Section: Introductionmentioning
confidence: 95%
“…The corrosion behavior of metal matrix composites and nanocomposites has been thoroughly investigated and reported [50][51][52][53][54] , however, it was not considered for hybrid ceramic matrix nanocomposites. Therefore, the corrosion rates of the alumina and Al 2 O 3 -5SiC-2CNT nanocomposite samples were compared with those of some metals and metal matrix nanocomposites 50,[55][56][57][58][59][60][61] and presented in Table 2. It can be clearly seen that the Al 2 O 3 and Al 2 O 3 -5SiC-2CNT nanocomposite have relatively low corrosion rates.…”
Section: Oda and Yoshiomentioning
confidence: 99%